2013
DOI: 10.1177/1470320313475906
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference of serum angiotensin-converting enzyme (ACE) activity in DD genotype of ACE insertion/deletion polymorphism in elderly Chinese

Abstract: Introduction: In this study we investigated the gender difference of serum angiotensin-converting enzyme (ACE) activity in a population of Hong Kong-dwelling elderly Chinese. Materials and methods: A total of 1767 (843 male, 924 female) Hong Kong-dwelling elderly Chinese were recruited. ACE I/D genotypes were identified by polymerase chain reaction amplification and serum ACE activity was determined using a commercially available kinetic kit. ACE I/D genotype distribution was compared by chi-square test, the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…There is an association between ACE gene polymorphism and the occurrence of CHD because the ACE D allele mutation results in higher ACE levels around blood vessels, generating more AngII and less bradykinin, leading to reductions in NO and prostacyclin. Other studies have confirmed this . Together, all these observations may explain, in part, the results regarding the therapeutic efficacy of salvianolate in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…There is an association between ACE gene polymorphism and the occurrence of CHD because the ACE D allele mutation results in higher ACE levels around blood vessels, generating more AngII and less bradykinin, leading to reductions in NO and prostacyclin. Other studies have confirmed this . Together, all these observations may explain, in part, the results regarding the therapeutic efficacy of salvianolate in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Angiotensin I converting enzyme (ACE) is a zinc metallopeptidase, which suggest that ACE could be involved in different physiological processes. The ACE serum level can be influenced by genetic factors (Zhang et al, ). The ACE I/D SNP has been significantly associated with serum ACE activity (Zhang et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The ACE serum level can be influenced by genetic factors (Zhang et al, ). The ACE I/D SNP has been significantly associated with serum ACE activity (Zhang et al, ). The ACE gene (I/D) was recently reviewed by Tian et al, consistent with HuGENet™ review study design and recommendations (Tian et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…This conversion along with additive effect of arterial hypertension may result in chronic kidney disease (19). Some studies point to the gender-dependent effect of ACE I/D polymorphism on blood ACE levels (20,21,22). Zhang et al suggested that in Asian population differences in blood ACE levels between DD genotype and other genotypes were more pronounced in men than in women (21).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies point to the gender-dependent effect of ACE I/D polymorphism on blood ACE levels (20,21,22). Zhang et al suggested that in Asian population differences in blood ACE levels between DD genotype and other genotypes were more pronounced in men than in women (21). Contrary, a study conducted by Biller and associates on Caucasian population reported the opposite results (22).…”
Section: Resultsmentioning
confidence: 99%